Laticifers distribution in secondary phloem of the Amazon wood specieswood species - Alonso, Alexandre Antonio; Mendonça, Maria Silvia; Reis, Renato Santos; Araújo Biondo, Pedro Luís Trevisan; Prata Alonso, Ressiliane Ribeiro (Comunicata Scientiae, 2013)
In this paper described the anatomical distribution of laticifers from the bark of Hura crepitans and Ficus maxima, typical floodplain trees in the Amazon forest. By observing samples which were processed by usual plant anatomy techniques, it was possible to verify that there were laticifers presenting radial distribution in the secondary stem phloem of F. maxima, and a diffuse distribution in the axial phloem in H. crepitans.